Implementasi Pendidikan STEM untuk Meningkatkan Hasil Belajar Siswa dalam Konsep Optik - Azhar Azhar; Dedi Irawan; Khaikal Ramadhan (Postgraduate, University of Mataram, 2022)
This paper reports the implementation of the STEM learning strategy to the 20 physics students on optical physics concepts. Previously, student understanding on this subject was categorized as weak, this was caused by not only learning just carried out theoretically but also the student's limitation to figure out the optical phenomenon. This research is to identify the student learning outcomes before and after STEM implementation by using simple experimental work with a set of pre-test and post-test. The calculation results show that the student's outcome has a medium enhancement which is about 0.53. Certainly, a Stem learning strategy is a good choice as a teaching strategy in the Optical Physics subject.